Relationships between the part of speech of the root and the productivity of nominal derivatives in Spanish and in Chinese - Zuo, Ya (Círculo de Lingüística Aplicada a la Comunicación, 2020)
This work, from a cognitive and contrastive perspective, attempts to study the relationship between the part of speech of the root and the productivity of Spanish and Chinese nominal derivatives. Combine quantitative and qualitative methods to explain the following phenomena: 1) in both languages, the deverbal derivative is more productive than the deadjectival derivatives; 2) the ability to change the grammatical category is more pronounced in Chinese than in Spanish; 3) In Chinese, denominal derivatives are the most productive and in Spanish, the deverbal ones. Based on the results obtained, we also provided some didactic suggestions in order to promote the teaching and learning of nominal derivatives in Spanish.